Prevalence of neutralising antibodies against SARS-CoV-2 in acute infection and convalescence: A systematic review and meta-analysis. - Helen R Savage; Victor S Santos; Thomas Edwards; Emanuele Giorgi; Sanjeev Krishna; Timothy D Planche; Henry M Staines; Joseph R A Fitchett; Daniela E Kirwan; Ana I Cubas Atienzar; David J Clark; Emily R Adams; et al. (Public Library of Science (PLoS), 2021)
Background Individuals infected with SARS-CoV-2 develop neutralising antibodies. We investigated the proportion of individuals with SARS-CoV-2 neutralising antibodies after infection and how this proportion varies with selected covariates. Methodology/principal findings This systematic review and meta-analysis examined the proportion of individuals with SARS-CoV-2 neutralising antibodies after infection and how these proportions vary with selected covariates. Three models using the maximum likelihood method assessed these proportions by study group, covariates and individually extracted data (protocol CRD42020208913). A total of 983 reports were identified and 27 were included. The pooled (95%CI) proportion of individuals with neutralising antibodies was 85.3% (83.5-86.9) using the titre cut off >1:20 and 83.9% (82.2-85.6), 70.2% (68.1-72.5) and 54.2% (52.0-56.5) with titres >1:40, >1:80 and >1:160, respectively. These proportions were higher among patients with severe COVID-19 (e.g., titres >1:80, 84.8% [80.0-89.2], >1:160, 74.4% [67.5-79.7]) than those with mild presentation (56.7% [49.9-62.9] and 44.1% [37.3-50.6], respectively) and lowest among asymptomatic infections (28.6% [17.9-39.2] and 10.0% [3.7-20.1], respectively). IgG and neutralising antibody levels correlated poorly. Conclusions/significance 85% of individuals with proven SARS-CoV-2 infection had detectable neutralising antibodies. This proportion varied with disease severity, study setting, time since infection and the method used to measure antibodies.